Active XML: application to the development of information systems curriculum - Vasilecas, Olegas; Saulis, Algis; Nogis, Rimvydas (Lietuvos matematikos rinkinys, 2003)
The paper deals with the problems of expanding the system of information systems curriculum development in the field of Web application. The main aim is to enhance the project coordination and control, to personalize presentation of information. Different active XML methods based on ECA (event-condition-action) model have been analyzed. All the methods discussed have drawbacks and limitations, and can be treated as prototypes of future universal system. Peer-to-peer architecture is recognized as the most suitable for active system. The results of investigation are implemented in a prototype that uses ideas of few methods.